A study on the micromechanical behaviors of duplex stainless steel under uniaxial tension using ex-situ experimentation and the crystal plasticity finite element method. (December 2015) - Jeong, C.U.; Heo, Y.-U.; Choi, J.Y.; Woo, W.; Choi, S.-H.
Abstract: An ex-situ experiment and a crystal plasticity finite element method (CPFEM) were used to investigate the micromechanical behaviors of a type of duplex stainless steel (DSS) that consisted of ferrite and austenite phases during uniaxial tension. An ex-situ experiment wherein tension testing and electron backscatter diffraction (EBSD) analysis were alternatively conducted was performed in order to measure the evolution of the initial microstructure in the DSS during uniaxial tension in the same region. A CPFEM based on the real microstructure simulated the micromechanical behaviors of the constituent phases in the DSS during uniaxial tension. The stress–strain relationships of the constituent phases were determined via in-situ neutron diffraction measurements in combination with the CPFEM based on simplified representative volume elements (RVEs). The heterogeneity of kernel average misorientation (KAM) is strongly dependent on the spatial distribution of constituent phases in the DSS. The KAM values of the austenite phase exhibited a relatively high distribution compared with those of the ferrite phase regardless of the amount of tensile strain. The CPFEM successfully predicted both the partitioning of the KAM in constituent phases in the DSS as well as the ductile fracture behavior during uniaxial tension, although the CPFEM failed to simulate the exact spatial evolution of the crystallographic orientation and the KAM in the constituent phases. Highlights: The micromechanical behaviors of the constituent phases in DSS were investigated. A technique of direct mapping of real microstructure into finite element meshes was used. CPFEM revealed the effect of initial microstructure on the micromechanical behaviors of DSS. CPFEM captures the heterogeneity of a kernel average misorientation (KAM). CPFEM successfully predicted the ductile failure behavior in the constituent phases of the DSS.